A spatial interaction model for agricultural uses - An application to understand the historical evolution of land use on a small island - Joana Gonçalves (European Regional Science Association (ERSA), 2005)
The agenda is to explain the historical evolution of land uses in small islands. First we assess the capacity of the island territory for different uses based on agronomic analysis and transform these capacities in attraction coeficients. Then we design a spatial interaction model with five different sectores which employment can be closely related with surface area. Finally we use historical data on population and main export crops in order to calibrate the model for each historical period. Therefore, based on data on the export crop and on the population it is possible to estimate the different land use of the island for all the sectors.
Keywords: 330